1992
DOI: 10.1152/jappl.1992.72.4.1512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training on elbow flexors of highly competitive bodybuilders

Abstract: The influence of gender on muscular adaptation of the elbow flexors to 24 wk of heavy resistance training was studied in five male bodybuilders (MB) and five female bodybuilders (FB) who were highly competitive. Muscle cross-sectional area (CSA), fiber area, and fiber number were determined from the biceps brachii, and voluntary elbow flexor torque was obtained at velocities of contraction between 0 and 300 degrees/s. Biceps and flexor CSA was 75.8 and 81% greater, respectively, in MB than in FB, but muscle CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 0 publications
4
30
0
3
Order By: Relevance
“…If the general principle regarding adaptation to stress applies, then muscle protein accretion ought to be progressively smaller as RT progresses [33,34]. Thus, it seems logical to expect an MPS response that would be either smaller in amplitude and/or duration in response to an RE bout in a T state compared with an UT state.…”
Section: Direct Comparison Between Training States For Muscle Proteinmentioning
confidence: 99%
“…If the general principle regarding adaptation to stress applies, then muscle protein accretion ought to be progressively smaller as RT progresses [33,34]. Thus, it seems logical to expect an MPS response that would be either smaller in amplitude and/or duration in response to an RE bout in a T state compared with an UT state.…”
Section: Direct Comparison Between Training States For Muscle Proteinmentioning
confidence: 99%
“…Muscle ®bre cross-sectional area (CSA) in highly trained male and female body builders have been found to be 147% and 54% greater, respectively, compared with untrained age matched controls (Alway et al 1992). It has been reported that the percentage increase in muscle hypertrophy in response to high intensity resistance training is similar for men and women (Cureton et al 1988;Davies et al 1988;O'Hagen et al 1995), although absolute increase in muscle CSA tends to be greater in men.…”
Section: Introductionmentioning
confidence: 99%
“…Women have a smaller cross-sectional area than males in both type I and II muscle Wbers (Alway et al 1989(Alway et al , 1992Miller et al 1992;Ryushi et al 1988;Staron et al 2000) with females' type I Wbers closer to their male counterparts in cross-section than are females' type II Wbers. Also, females' type I Wbers can be equivalent or even larger in cross-sectional area than their type II Wbers (Alway et al 1989;Staron et al 1989Staron et al , 2000.…”
Section: Discussionmentioning
confidence: 97%